2015
DOI: 10.1073/pnas.1419168112
|View full text |Cite
|
Sign up to set email alerts
|

TRAPPII regulates exocytic Golgi exit by mediating nucleotide exchange on the Ypt31 ortholog RabE RAB11

Abstract: The oligomeric complex transport protein particle I (TRAPPI) mediates nucleotide exchange on the RAB GTPase RAB1/Ypt1. TRAPPII is composed of TRAPPI plus three additional subunits, Trs120, Trs130, and Trs65. Unclear is whether TRAPPII mediates nucleotide exchange on RAB1/Ypt1, RAB11/Ypt31, or both. In Aspergillus nidulans, RabO RAB1 resides in the Golgi, RabE RAB11 localizes to exocytic post-Golgi carriers undergoing transport to the apex, and hypA encodes Trs120.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
105
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(110 citation statements)
references
References 52 publications
4
105
1
Order By: Relevance
“…First, we have shown that Ypt1 mutants used to implicate Ypt1 in late-Golgi transport (Sclafani et al, 2010) are instead defective in autophagy (Lipatova et al, 2013). Second, in vitro and in vivo studies support a role for TRAPP II at the late Golgi as a GEF for the S. cerevisiae Ypt31 (Morozova et al, 2006) and its Aspergillus nidulans ortholog RabE RAB11 (Pinar et al, 2015). Thus, our and others cumulative data reinforce the idea that TRAPP I-stimulated Ypt1 regulates transport at the early Golgi, whereas TRAPP II-activated Ypt31/32 regulate transport at the late Golgi.…”
Section: Discussionmentioning
confidence: 97%
“…First, we have shown that Ypt1 mutants used to implicate Ypt1 in late-Golgi transport (Sclafani et al, 2010) are instead defective in autophagy (Lipatova et al, 2013). Second, in vitro and in vivo studies support a role for TRAPP II at the late Golgi as a GEF for the S. cerevisiae Ypt31 (Morozova et al, 2006) and its Aspergillus nidulans ortholog RabE RAB11 (Pinar et al, 2015). Thus, our and others cumulative data reinforce the idea that TRAPP I-stimulated Ypt1 regulates transport at the early Golgi, whereas TRAPP II-activated Ypt31/32 regulate transport at the late Golgi.…”
Section: Discussionmentioning
confidence: 97%
“…TRAPP tethering complexes are known to act as guanine exchange factors (GEFs) and, thus, activate RAB GTPases (Jones et al, 2000;Wang et al, 2000;Pinar et al, 2015). Colocalization at the TGN and functional studies suggest that TRAPPII acts as a GEF for RABA1c, facilitating RABA1c-mediated trafficking of material from the TGN to the cell plate (Qi et al, 2011).…”
Section: Tgn and The Cell Plate: A Timely Connectionmentioning
confidence: 99%
“…Interestingly, the TRAPPII-binding N-terminal domain of Rabin8 is absent from Sec2 (yeast homolog of Rabin8). As TRAPPII mediates nucleotide exchange on the Ypt31 ortholog RabERAB11 53 , it could also function as a GEF for vertebrate Rab11. TRAPPC10 has a longin domain (LD) that forms a platform for small GTPases in Rab GEFs 54 , and a conserved, centrosome-targeting ASH domain 55 .…”
Section: Cilia Targeted Trafficking Complexesmentioning
confidence: 99%